BENTUK KERJASAMA GURU BK DENGAN GURU MATA PELAJARAN DALAM MEMBINA MORAL PESERTA DIDIK KELAS IX DI SMP NEGERI 1 PAINAN - SARI, SHERLYE NOFIA (Bimbingan dan Konseling, 2014)
However because itâs still not applied yet in that school, a research was done in order to describe: 1) The forms of cooperation between counselor with class teachers in students morale education in view of action learning approach, 2) The forms of cooperation between counselor with class teachers in students morale education in view of cognitive development approach. The quantitative descriptive type research is used with certain population of 204 with 41 sample. Sample was taken using proportional random sampling technique. This research instrument is in the form of quistionnaire. Data analysis is processed with kriterium sturgess and persentative formulation. Research results prove that: 1) Forms of cooperation between counselor with class theachers in students moral education of class IX considering action learning approach is in the good category, 2) The forms of cooperation between counselor with class teachers in students moral education of class IX considering cognitive development is in the passable category.